How Beliefs and Performance Influence Professional Identity Formation: Insight from Indonesian ELT Graduate Student - Sintia Marlina Urbaq; Ngadiso; Dewi Rochsantiningsih (Didaktika: Jurnal Kependidikan, 2025)
Master's programs present a unique challenge to professional identity development. Students concurrently engage in academic pursuits, research activities, and frequently part-time employment. This confluence of responsibilities creates a dynamic environment where role conflict can disrupt the clarity and coherence of their developing professional identity. The purpose of this research was to explore the development of professional identity among Master's students, focusing on the interplay between their beliefs about their identity image and their actual performance in identity development activities. This study explored two key aspects of ELT graduate student development: How do ELT graduate students envision themselves as future educators? and What strategies do ELT graduate students employ to develop their professional competence? This study utilized a qualitative approach to amplify the data derived from participants' own words through in-depth descriptions of their experiences. The data for this study was ELT graduate students who actively pursued master's programs. Moreover, the researchers s used interactive model analysis to analyze the data. This study revealed two key findings related to the research question: 1) Students envision themselves as effective teacher: 2) Professional identity development through academic and non-academic activities. This study implies that PID is a continuous process requiring ongoing learning and growth. ELT graduate students should actively engage in professional development and utilize structured self-reflection (e.g., journals, portfolios) to identify strengths and weaknesses.